PRODUCTIVITY OF LABOR IN UKRAINE: MOTIVATIVE ASPECT - Кочума, Інна (Socio-economic relations in the digital society, 2019)
The article analyses dynamic and main factors of low productivity of labor in Ukraine. The research examines reasons of self-reproduction of low incentives to its increase both at the state level and at the level of employers and employees. It proposes changes to the domestic institutional environment as the main precondition for formation of a motivational mechanism for improving of labor productivity. Relevance of this study is determined by a need to increase efficiency of labor in Ukraine as a prerequisite for ensuring high pace of economic growth and a high level of well-being of Ukrainian citizens.